Detection of untreated mycobacteria by using polymerase chain reaction and specific DNA probes. - Fries, J W (1991)
A method for specific identification of mycobacteria by using the polymerase chain reaction on organisms taken from liquid cultures, frozen suspensions, or colonies grown on Lowenstein-Jensen slants is presented. This direct detection of mycobacterial organisms has important implications for strain typing and diagnosis.